English Use In Al-Amien Islamic Boarding School Prenduan Sumenep Madura - Zainuddin Zainuddin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
The research discusses English Use in Al-Amien Islamic Boarding School Prenduan Sumenep Madura. The research says that the VI class students of Marhalah Aliyah TMI Putra Al-Amien Islamic Boarding School Prenduan Sumenep Madura do not pronounce the given aimed words in the sentence bases word stressed syllables of English. The research is designed as qualitative research with descriptive method. Within, the researcher takes observation, interview, and test for instrument of data collection. Here, the data is taken from Marhalah Aliyah TMI Putra Al-Amien Islamic Boarding School Prenduan Sumenep Madura students. There are 204 students from VI class: four classes for Dirasah Islamiyah Wal Arabiyah (DIA), one class for Matematika dan IPA (MIPA) and another one class for IPS dan Bahasa Inggris (IPSI). Five students are taken from each class as respondents through purposive sampling and another Six interviewees for primary data. In conclusion, the research says that the VI class students of Marhalah Aliyah TMI Putra Al-Amien Islamic Boarding School Prenduan Sumenep Madura do not pronounce the given aimed words in the sentence bases word stressed syllables of English.